2016
DOI: 10.5713/ajas.16.0589
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of isolated lactic acid bacteria and their effects on the silage quality

Abstract: ObjectiveFour lactic acid bacteria (LAB) strains isolated from common vetch, tall fescue and perennial ryegrass on the Tibetan Plateau were characterized, and their effects on the fermentation quality of Italian ryegrass (Lolium multiflorum Lam.) silage were studied.MethodsThe four isolated strains and one commercial inoculant (G, Lactobacillus plantarum MTD-1) were evaluated using the acid production ability test, morphological observation, Gram staining, physiological, biochemical and acid tolerance tests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The organic acid contents were analysed by high‐performance liquid chromatography (HPLC) according to the method described by Wang et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic acid contents were analysed by high‐performance liquid chromatography (HPLC) according to the method described by Wang et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Ammonia nitrogen (NH 3 -N) was determined according to Chen et al (2014). The organic acid contents were analysed by high-performance liquid chromatography (HPLC) according to the method described by Wang et al (2017).…”
Section: Chemical and Microbiological Analysesmentioning
confidence: 99%
“…Fermented shrimp waste contained 10% of glucose and 5% of various types of starter cultures had higher than 63 mg lactic acid/g and up to 6 mg acetic acid/g, when samples were allowed to ferment at 30 • C for 48 h [41]. Raw fish processing waste had the lowest amount of acetic acid, although among silage groups, the highest acetic acid formation was observed in the acid silage group of fish processing waste, with a corresponding value of 1022.62 mg/100 g. Wang et al [42] reported that Italian ryegrass silages inoculated with a commercial L. plantarum strain contained a higher ratio of lactic and acetic acids (13.53) than those observed with LAB strains isolated from common vetch, tall fescue, and perennial ryegrass silages undertaken at 25 • C. However, the silages inoculated with P. acidilactici, Lactobacillus paraplantarum, and Lactobacillus casei isolates and developed at 10 • C and 15 • C revealed higher ratios of lactic and acetic acids (8.79, 7.95, and 5.87 for 10 • C; 8.23, 5.87, and 5.52 for 15 • C, respectively) than the silages inoculated with commercial LAB strains [42]. In the current study, the acetic acid in fermented silages was metabolized in the range from 447.15 mg/100 g, in the silage of gibel carp by Lb.…”
Section: Organic Acids In Wet Fish-based Silagesmentioning
confidence: 96%
“…In general, silage fermentation is influenced by the role of lactic acid bacteria (LAB) during ensiling. A previous study reported that silage inoculated with a homo fermentative LAB enhanced the fermentation quality [ 9 ], while a hetero fermentative LAB improved the aerobic stability [ 10 ]. The combination of homo and hetero fermentative LAB improved not only fermentation quality, but also aerobic stability [ 11 ].…”
Section: Introductionmentioning
confidence: 99%